An Eco-Morphodynamic Modelling Approach to Estuarine Hydrodynamics & Wetlands in Response to Sea-Level Rise - Kumbier, Kristian; Rogers, Kerrylee; Hughes, Michael G.; Lal, Kirti K.; Mogensen, Laura A.; Woodroffe, Colin D. (Frontiers in Marine Science, 2022)
Tidal inundation is the primary driver of intertidal wetland functioning and will be affected by sea- level rise (SLR). The morphology of estuaries and friction across intertidal surfaces influences tidal propagation; accordingly, sea-level rise not only increases inundation frequency, but will also alter other tidal parameters, such as tidal range. To investigate responses of estuarine intertidal vegetation, primarily mangrove and saltmarsh, to SLR an eco-morphodynamic modelling approach was developed that accounted for some of the feedbacks between tidal inundation and changes to wetland substrate elevations. This model partially accounts for adjustment in estuarine hydrodynamics, and was used to examine the potential effect of SLR on mangrove and saltmarsh distribution in a micro-tidal channelised infilled barrier estuary in southeast Australia. The modelling approach combines a depth-averaged hydrodynamic model (Telemac2D) and an empirical wetland elevation model (WEM) that were coupled dynamically to allow for eco-geomorphological feedbacks. The integrated model was parameterised to consider two SLR scenarios, and two accretion scenarios within the WEM. Time series of observed water levels, tidal inundation and flow velocity were used to validate the hydrodynamic model for present-day sea level, whereas wetland mapping was used to verify predictions of mangrove and saltmarsh distribution. Tidal range varied along the estuary, increasing in response to low and high SLR scenarios (by up to 8%), and responded non-linearly under high SLR. Simulations of low and high SLR scenarios indicated that wetlands mostly withstand modest SLR rates (+ 5mm yr-1) through sedimentation, but submerge and convert to subtidal areas under fast SLR rates (> 10mm yr-1). Projected changes in tidal range are linked to eco-geomorphological feedbacks caused by changing wetland extents and adjustments of intertidal wetland geomorphology through sedimentation. Potential changes arising from morphological change at the entrance and in the tidal channels is not obtained from the model. The results of this study demonstrate interconnections between hydrodynamics and intertidal wetlands, which need to be accounted for when estimating wetland response to SLR in channelised estuaries. Integrated models of estuarine-wetland systems are more precise as they account for the dynamic feedbacks between hydrodynamics and wetlands. For example, they also consider alterations to tidal range resulting from SLR and the effects of these on wetland inundation and sedimentation.